Gas hydrate exploitation using CO2/H2 mixture gas by semi-continuous injection-production mode. (15th April 2019) - Sun, Yi-Fei; Wang, Yun-Fei; Zhong, Jin-Rong; Li, Wen-Zhi; Li, Rui; Cao, Bo-Jian; Kan, Jing-Yu; Sun, Chang-Yu; Chen, Guang-Jin
Highlights: A novel NGH exploitation method by CO2 /H2 semi-continuous injection-production was proposed. CH4 recovery and concentration were enhanced dramatically when injecting low CO2 concentration. Fast CH4 hydrate decomposition stage can be retained separately in the replacement process. A circulating injection-production strategy was beneficial to CO2 storage with high CH4 recovery. Abstract: The CO2 replacement technique is considered as a promising approach for both gas hydrate recovery and CO2 sequestration. Based on this technique, the continuous CO2 /H2 injection-production mode had been studied in our previous work. However, there are limitations on this continuous mode, such as lower CH4 recovery and CO2 sequestration ratios, lower CH4 concentration in produced gas and higher injection-production ratio caused by the fast breakthrough of injected gas. Here we proposed a so called semi-continuous injection-production mode, in which continuous injection-production process is interrupted periodically by stopping injection and production operations for letting injected gas diffuse sufficiently, delaying its breakthrough and increasing its effective sweep region. A series of experimental simulations were performed with respect to this mode in a three-dimensional simulator with a volume of 10.6 L. The results indicated that for the injected gas with low CO2 concentration, the CH4 recovery and concentration in the produced gas could be enhanced dramatically by the semi-continuous gas injection method. Additionally, the fast decomposition stage of CH4 hydrate could be retained separately in the replacement process, thereby effectively improving production efficiency. However, the corresponding CH4 concentration in the produced gas decreased and the injection production ratio increased. Notably, the process combining the CH4 steam reforming with cyclic injection-production was first simulated. The results showed an excellent CO2 storage capability and CH4 hydrate recovery ratio, which was mainly controlled by the gas composition of the re-injected gas. Through systematically comparing and analyzing the CH4 concentration, recovery ratio, production efficiency and injection-production ratio, it is demonstrated that the semi-continuous injection-production mode is superior to the continuous one. The results obtained in this work are of significance for guiding future NGHs exploitation.